An Overview of Covid-19 Dedicated Scientific Databases - Meisam Dastani (Mashhad University of Medical Sciences, 2021)
The rapid and challenging spread of the COVID-19 virus disease has become a significant threat in all countries of the world, which has provoked immediate reactions from the scientific and medical society and led to scientific publications on various aspects of the disease.  Therefore, quick and easy access to these publications' results and sharing scientific data and findings to understand the disease control and create treatments and vaccines is one of the biggest ways to quickly and usefully transmit research results. The purpose of the present narrative review is to introduce the dedicated scientific databases of COVID-19 disease. For this purpose, an appropriate search was used to extract the studies conducted in the Google Scholar and PubMed databases. In the results, 16 databases of COVID-19 disease have been identified and introduced. Researchers are able to use these resources for their science and research purposes in accordance with the tools and capabilities available in the COVID-19 databases provided in this report.